Trafficking women for sexual exploitation: a systematic review - Gomes, Sofia Patrício (2023)
Human trafficking is a complex global problem that demands current and scientifically grounded knowledge capable of coordinating interventions among various sectors of society. To address this issue, a systematic collection of scientific articles was conducted in two databases (Web of Science and Scielo) using keywords in both English and Portuguese. After screening 267 articles based on title, abstract, and full text, an 11-article sample was analyzed for quality. The results revealed that conceptual inconsistency is a challenge in signaling human trafficking, particularly in cases of sexual exploitation of women where it may be associated with prostitution, pimping, or migration—all of which are activities tied to financial gain. Addressing human trafficking requires action from concept to practice, including strengthened policies for sanctions and necessary support for victims.